The adsorption of lysozyme at the silica-water interface: A neutron reflection study - Su, T; Lu, JR; Thomas, R; Cui, Z; Penfold, J (1998)
The adsorption of lysozyme (chicken egg white) from aqueous solution on to the hydrophilic silica surface and the variation of interfacial structure with solution conditions have been studied by neutron reflection. The accurate determination of the adsorbed layer thicknesses in combination with the dimension of the globular structure of lysozyme allows us to postulate the mean structural conformation of the lysozyme molecules within the adsorbed layer. It was found that the adsorption was completely reproducible with respect to lysozyme concentration, but it was irreversible. The effect of ionic strength on the adsorption of lysozyme was examined at pH 7 and at a bulk lysozyme concentration of 0.03 g dm-3. The adsorbed layer was not affected by changes in ionic strength i when the total ionic strength was below 0.05 M, but above this t concentration addition of NaCl gradually reduced the amount of lysozyme adsorbed. Complete removal of adsorbed lysozyme was achieved when the total ionic strength was above 0.5 M. The effect of solution pH on the amount of lysozyme adsorbed was characterized by varying the pH in cycles at fixed lysozyme concentrations. Adsorption was found to be completely reversible with respect to pH over a wide protein concentration range. The level of surface excess was dominated by the electrostatic repulsion between lysozyme molecules within the adsorbed layers, rather than the at- traction between the surface and lysozyme. The lysozyme layer structure along the surface normal was characterized by varying the isotopic composition of the water. At pH 7 a monolayer 30 ± 2 AÅ thick was formed when the lysozyme concentration was below 0.03 g dm-3, indicating that the lysozyme was adsorbed with its long axis parallel to the surface (sideways-on). At higher concentrations the thickness of the layer changed to 60 ± 2 AÅ, suggesting the formation of a bilayer of lysozyme molecules in the sideways- on configuration. When the lysozyme concentration is above 1 g dm-3 the surface excess within the inner layer is sufficiently high that repulsion within the adsorbed layer becomes significant and the molecules start to tilt towards longways-on adsorption. At pH 4, the electrostatic repulsion between the adsorbed molecules is stronger than at pH 7, resulting in a lower surface excess and a tilting away from the sideways-on configuration at lower surface concentration.